Pengaruh Metode Realistic Mathematics Education terhadap Kemampuan Berpikir Kritis Siswa pada Materi Penjumlahan dan Pengurangan di SDN 3 Simpen - Virdaus, Alvian; Gunawan, Dani; Jenal Mutaqin, Ejen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are among the skills that need to be developed in mathematics education; however, these skills remain relatively low among elementary school students, particularly when solving addition and subtraction word problems. This study aims to determine the effect of implementing the Realistic Mathematics Education (RME) method on students’ critical thinking skills in addition and subtraction topics in third grade at SDN 3 Simpen. The study employed a quantitative approach using a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 31 third-grade students at SDN 3 Simpen during the 2025/2026 school year. Data were collected using critical thinking ability tests in the form of pretests and posttests, which were then analyzed through normality tests and hypothesis testing. The results of the study show that students’ average critical thinking scores increased from 28.226 on the pretest to 81.855 on the posttest. The normality test results indicated that the data were not normally distributed; therefore, hypothesis testing was conducted using the Mann–Whitney test. The test results indicate that H₀ was rejected and Hₐ was accepted, meaning that the implementation of the Realistic Mathematics Education method has an effect on students’ critical thinking skills in addition and subtraction. Thus, the Realistic Mathematics Education method can serve as an effective alternative teaching method to improve the critical thinking skills of elementary school students.